2007
DOI: 10.1088/1742-5468/2007/06/p06019
|View full text |Cite
|
Sign up to set email alerts
|

A supercritical series analysis for the generalized contact process with diffusion

Abstract: We study a model that generalizes the CP with diffusion. An additional transition is included in the model so that at a particular point of its phase diagram a crossover from the directed percolation to the compact directed percolation class will happen. We are particularly interested in the effect of diffusion on the properties of the crossover between the universality classes. To address this point, we develop a supercritical series expansion for the ultimate survival probability and analyse this series usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Using the perturbative supercritical series expansion formalism, proposed by Dickman and Jensen [5], we obtain a very precise estimates for this exponent in a generalized contact process (CP) model, * Electronic address: wgd@gibbs.if.usp.br † Electronic address: oliveira@if.usp.br ‡ Electronic address: jstilck@if.uff.br which lead us to conjecture that φ = 2, in accordance with upper bound estimates [10] and simulational results for the Domany-Kinzel cellular automaton [11], which may indicate that this exponent is the same for similar models with paralell and sequencial updates. However, in an extended version of the generalized model (including a diffusion process) we were not be able to determine the behavior of the crossover exponent φ as a function of the diffusion rate in the limit of high diffusion rate [12]. Our results show only that, in a region of weak diffusion, the crossover exponent still is φ = 2.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Using the perturbative supercritical series expansion formalism, proposed by Dickman and Jensen [5], we obtain a very precise estimates for this exponent in a generalized contact process (CP) model, * Electronic address: wgd@gibbs.if.usp.br † Electronic address: oliveira@if.usp.br ‡ Electronic address: jstilck@if.uff.br which lead us to conjecture that φ = 2, in accordance with upper bound estimates [10] and simulational results for the Domany-Kinzel cellular automaton [11], which may indicate that this exponent is the same for similar models with paralell and sequencial updates. However, in an extended version of the generalized model (including a diffusion process) we were not be able to determine the behavior of the crossover exponent φ as a function of the diffusion rate in the limit of high diffusion rate [12]. Our results show only that, in a region of weak diffusion, the crossover exponent still is φ = 2.…”
Section: Introductionmentioning
confidence: 56%
“…In a preliminar work [12], using perturbative series approach, we determine the value φ ≈ 2 up to D ≈ 0.3 and due to limitations in the series derivation, we were not able to reach larger values for the diffusion rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
In a recent work, Dantas and Stilck studied a model that generalizes the contact process model with diffusion [1]. Our approach, based on the supercritical expansion, showed that for a weak diffusion regime the crossover exponent between the directed percolation and compact directed percolation universality classes was φ ≈ 2.
…”
mentioning
confidence: 99%